Policy Perspective of Taxation of Income during Post Liberalization Period: Challenges and Recommendations for the Income Tax System (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present examination looks at the Taxation of Income in India amid post liberalization period and policy perspective in such manner. It has dissected the development of income tax income, execution of Income Tax Department and impression of tax experts with respect to Income Tax System in India. For assessing development of income tax income in India and execution of the income tax administration optional information has been gathered for the period 1997-98 to 2007-08. Further, a greater part of tax experts opined that tax avoidance and defilement are common in the Indian Income Tax System because of numerous taxes, high tax rates, social acknowledgment of tax avoidance, low likelihood of recognition and low tax ethical quality, extreme optional forces accessible with income tax specialists. They opined that staff is accessible in the workplaces and labor is overburdened in Income Tax Department. Nonetheless, they additionally opined that Income tax administration isn't taxpayer neighborly. With respect to rates they opined that tax rates are sensible for people and HUFs however these are high for AOPs and BOIs, firms and organizations. They likewise brought up that confused tax law, high tax rates, defilement, high consistence cost and protracted return frames are the significant issues looked by the customers. The investigation closes with specific recommendations for enhancing Income Tax System.